Patient-derived cells from recurrent tumors that model the evolution of IDH-mutant glioma. Issue 1 (16th July 2020) - Jones, Lindsey E; Hilz, Stephanie; Grimmer, Matthew R; Mazor, Tali; Najac, Chloé; Mukherjee, Joydeep; McKinney, Andrew; Chow, Tracy; Pieper, Russell O; Ronen, Sabrina M; Chang, Susan M; Phillips, Joanna J; et al.
Abstract: Background: IDH- mutant lower-grade gliomas (LGGs) evolve under the selective pressure of therapy, but well-characterized patient-derived cells (PDCs) modeling evolutionary stages are lacking. IDH -mutant LGGs may develop therapeutic resistance associated with chemotherapy-driven hypermutation and malignant progression. The aim of this study was to establish and characterize PDCs, single-cell-derived PDCs (scPDCs), and xenografts (PDX) of IDH1 -mutant recurrences representing distinct stages of tumor evolution. Methods: We derived and validated cell cultures from IDH1- mutant recurrences of astrocytoma and oligodendroglioma. We used exome sequencing and phylogenetic reconstruction to examine the evolutionary stage represented by PDCs, scPDCs, and PDX relative to corresponding spatiotemporal tumor tissue and germline DNA. PDCs were also characterized for growth and tumor immortality phenotypes, and PDX were examined histologically. Results: The integrated astrocytoma phylogeny revealed 2 independent founder clonal expansions of hypermutated (HM) cells in tumor tissue that are faithfully represented by independent PDCs. The oligodendroglioma phylogeny showed more than 4000 temozolomide-associated mutations shared among tumor samples, PDCs, scPDCs, and PDX, suggesting a shared monoclonal origin. The PDCs from both subtypes exhibited hallmarks of tumorigenesis, retention of subtype-defining genomic features, production of 2-hydroxyglutarate, and subtype-specific telomere maintenance mechanisms that confer tumor cell immortality. The oligodendroglioma PDCs formed infiltrative intracranial tumors with characteristic histology. Conclusions: These PDCs, scPDCs, and PDX are unique and versatile community resources that model the heterogeneous clonal origins and functions of recurrent IDH1 -mutant LGGs. The integrated phylogenies advance our knowledge of the complex evolution and immense mutational load of IDH1 -mutant HM glioma.